LncRNA NEAT1 promotes MPP+ induced injury of PC12 cells and accelerates the progression of Parkinson's disease in mice through FUS mediated inhibition of PI3K/AKT/mTOR signalling pathway - Yonghui Wang; Zhuo Li; Jiwen Li; Chao Sun (Experimental Gerontology, 2024)
Long noncoding RNA nuclear-enriched abundant transcript 1 (NEAT1) is involved in the progression of Parkinson's disease (PD), but the specific regulatory role needs further exploration. This study showed that the expression of NEAT1 was upregulated in the cerebrospinal fluid (CSF) and peripheral blood of patients with different stages of PD. 1-Methyl-4-phenylpyridine (MPP)-treated PC 12 cells were transfected with si-NEAT1, and MPP treatment promoted cell apoptosis, oxidative stress and inflammatory factor secretion. Si-NEAT1 reversed the effects of MPP. NEAT1 silencing eliminated the effect of MPP on the protein expression levels of LC3-II and p62/SQSTM1. By using an online bioinformatics database, Fused in Sarcoma (FUS) was confirmed to be an RNA binding protein of NEAT1, and it was highly expressed in the CSF and peripheral blood of patients with PD. Si-FUS was transfected into MPP-treated PC 12 cells to detect cell apoptosis, oxidative stress, inflammatory factor secretion and autophagy, and the results were the same as those of transfection of si-NEAT1. Furthermore, MPP treatment reduced the phosphorylation levels of PI3K, Akt and mTOR, whereas si-FUS reversed the effects of MPP. In vivo, compared with the model group, the PD mice showed reduced NEAT1 and FUS expression levels and activated PI3K pathway after being injected with si-NEAT1. The brain tissue of NEAT1-silenced PD mice had decreased inflammatory infiltration and apoptosis and increased neurological scores. In conclusion, NEAT1 is involved in PD progression through FUS-mediated inhibition of the PI3K/AKT/mTOR signalling pathway.